If not police, then who? Building a new workforce for community behavioral health crisis response - Watson, Amy C.; McNally, Kellan; Pope, Leah G.; Compton, Michael T. (Frontiers in Psychology, 2025)
IntroductionCommunities across the United States and elsewhere are working to implement alternatives to law enforcement as primary responders to behavioral health crises. These efforts can only be successful if there is a skilled workforce prepared to take on this role. We argue that this workforce must be developed, and propose a new, credentialed Community Behavioral Health Crisis Responder (CBHCR) role.MethodsGuided by a 13-member advisory board with expertise across behavioral health, crisis services, and law enforcement, we conducted a literature review, key informant interviews, and focus groups to identify the foundational values, competencies, and skills for this proposed role.ResultsInterview and focus group participants discussed desired characteristics of CBHCRs and emphasized values such as cultural humility, a nonjudgmental approach, and the importance of lived experience broadly defined. Competencies and skills included engagement and communication strategies that enhance safety and trust, suicide prevention, conflict resolution, and situational awareness. Participants highlighted the need to train CBHCRs to provide compassionate, trauma-informed crisis intervention, de-escalation, support, and connection to needed resources. In conjunction with our advisory board and external experts, we used the findings to iteratively refine the values, competencies, and skills of CBHCRs.DiscussionWe discuss the next steps in creating this new, skilled and credentialed crisis response workforce.